The Goodbye Letter - Mall, Shireen (WritingThreeSixty, 2018)
The Goodbye Letter is a short work of fiction, which seeks to capture a number of important episodes in John, my deceased father’s life. It is a dialogue using biography and the tools and traditional mediums of biography like letters, clips, journal entries and photos, combined with memory and imagination. By combining archive material in my possession with my own imagined extensions and re- inventions of memories that John recounted to me while he was still alive, or which I myself was privy to, I hope to stitch together a coherent yet simultaneously fragmented representation of episodes in my enigmatic father’s life in Cape Town during the apartheid years.